Ovarian Torsion in a 5-Year Old: A Case Report and Review. (7th June 2012) - Ryan, Matthew F.; Desai, Bobby K.
Abstract : Ovarian torsion represents a true surgical emergency. Prompt diagnosis is essential to ovarian salvage, and high clinical suspicion is important in this regard. Confounding the diagnosis in general are more commonly encountered abdominal complaints in the Emergency Department (ED) such as constipation, diarrhea, and urinary tract infections and more common surgical emergencies such as appendicitis. Prompt diagnosis can be further complicated in low-risk populations such as young children. Herein, we describe the case of a 5-year-old girl with a seemingly benign presentation of abdominal pain who was diagnosed in the ED and treated for acute ovarian torsion after two prior clinic visits. A brief discussion of evaluation, treatment, and management of ovarian torsion follows.